2001
DOI: 10.1016/s0169-5150(01)00092-5
|View full text |Cite
|
Sign up to set email alerts
|

A fresh meat almost ideal demand system incorporating negative TV press and advertising impact

Abstract: Agricultural Economics 25 (2001) 359-374. doi:10.1016/S0169-5150(01)00092-52016-03-04T18:47:27

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 16 publications
2
100
3
1
Order By: Relevance
“…The sector is mainly concerned about false communications that relate the vaccine to a hormone treatment. Previous research has already indicated the strong negative impact such communication can have on consumer attitudes and meat purchasing behaviour (Verbeke and Ward, 2001;Verbeke et al, 2002). No such indications of adverse consumer responses to the vaccine method were found in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…The sector is mainly concerned about false communications that relate the vaccine to a hormone treatment. Previous research has already indicated the strong negative impact such communication can have on consumer attitudes and meat purchasing behaviour (Verbeke and Ward, 2001;Verbeke et al, 2002). No such indications of adverse consumer responses to the vaccine method were found in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…self-directed v. other-directed) (39) (for discussion on health-motive orientations, see later), as well as the message's overall appeal to positive (benefits) v. negative (risks) outcomes determines its processing and effectiveness. A similar quantity of unfavourable news or negative news dealing, for example, with food safety risks weighs more heavily in consumer decision making than favourable news (21,(40)(41)(42) , e.g. information concentrating on nutritional and health benefits.…”
Section: Message Type and Contentmentioning
confidence: 99%
“…Previous studies assessed that negative media messages about food can have a considerable impact on purchasing choices (48)(49)(50) . Moreover, it has been suggested that negative press has an impact five to seven times stronger on purchasing behaviours than favourable press (51,52) . Hence, a possible impact of the La Repubblica coverage on fish consumption patterns of its readers could be a reduction in fish intake; which, in turn, would lead to a decrease in the health benefits related to fish consumption.…”
Section: Discussionmentioning
confidence: 99%